Investigating the Perceived Care Burden of Nurses Caring for COVID-19 Patients - Mirrashidi, Fateme Sadat; Askarpour, Hedie; Shokoufamanesh, Ayuob; Raesi, Rasoul; Hushmandi, Kiavash; Razzaghi, Alireza; Shafaei, Fatemeh; Daneshi, Salman (Coronaviruses, 2025)
<span class=
Keywords: nurse